A report of the Laikipia elephant count, 1990 - Chris Thouless (Pachyderm)
A total count of elephants in Laikipia District and the adjoining parts of western Isiolo and southern Samburu Districts carried out in 1990 suggests an minimum population of approximately 2000. Much of Laikipia consists of large-scale private ranch lands, and it is in these areas that Kenya's second largest elephant population exists. The presence of these elephants has caused many management problems, and KWS devised the Laikipia Elephant Project to tackle some of these. The format and the results of the total aerial count, which yielded a figure of 2045 animals, carried out in mid Sepetember is discuss.